Enhanced screening via a pure DNA-encoded peptide library enabled by an Fmoc modification - Qiujin He; Yanhui Wang; Xiyuan Tang; Jianwei Zhang; Yuyu Xing; Zhaoyun Zong; Mohamed A. Elhamouly; Kaixian Chen; Shiyu Chen (Proceedings of the National Academy of Sciences, 2026)
Peptide-based molecules have widespread therapeutic applications due to their potent binding affinity and relative metabolic safety. Peptide therapeutics are developed using library screening that samples a diverse chemical space within primary sequences and secondary structural conformations. DNA-encoded peptide libraries (PDELs) are ideal for the development of peptide-based therapeutics as novel building blocks, and diverse chemical modifications are easily incorporated. However, current PDEL construction is limited by precipitation-based purification, which constrains libraries to three or four building blocks in length due to decreasing quality with each synthetic step. Herein, we developed a solid-phase capture-based purification method to generate longer PDELs with increased purity. We modified the conventional Fmoc protecting group with an azido handle to introduce click chemistry for selective immobilization during purification. Using this method, we achieved >95% purity in the synthesis of a five-round PDEL that showed great efficiency in identifying high nanomolar binders against transferrin receptor protein 1. This work delivers a scalable and robust platform for generating high-quality, noncanonical peptide libraries, which marks a major breakthrough in peptide-based drug discovery.